If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 15y + -11 Reorder the terms: 6 = -11 + 15y Solving 6 = -11 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 6 + -15y = -11 + 15y + -15y Combine like terms: 15y + -15y = 0 6 + -15y = -11 + 0 6 + -15y = -11 Add '-6' to each side of the equation. 6 + -6 + -15y = -11 + -6 Combine like terms: 6 + -6 = 0 0 + -15y = -11 + -6 -15y = -11 + -6 Combine like terms: -11 + -6 = -17 -15y = -17 Divide each side by '-15'. y = 1.133333333 Simplifying y = 1.133333333
| (a-2)-3(2a-1)=13 | | LN0.1/(-0.0244) | | x-.20x=25.60 | | (2x-y)(x+y)=0 | | =0.022 | | x-.20=23.20 | | 5x+2+3y=42+87 | | a^2-16a-7=0 | | 2(w+3)=8 | | (3y-1)+(4y+7)= | | -80-10x=140 | | ln(2x+1)=3.25 | | 4u-26=-2(u+7) | | -10x-35+24x=6x+13 | | x+x+75+x-15=180 | | X+13x+42= | | 2lnx=ln(x+2) | | 205/x=5.54 | | 5(3x+2)-2=4(4x-3) | | (4/x^2) | | 23x+2y=-19 | | -3(-2x-2)=12 | | 2.6=3a | | 7b-10+69-3=83 | | y-42=180 | | 8(1+5)+5=12+5x | | 1-4lnx=lnx-9 | | 10f+8=11f+7 | | 6(y+1)=2y+18 | | 4m+10=36 | | 23+5x=111-3x | | 7(51)=10 |